Radio‐guided occult lesion localisation using iodine 125 Seeds "ROLLIS" to guide surgical removal of an impalpable posterior chest wall melanoma metastasis. Issue 3 (3rd September 2015) - Dissanayake, Shashini; Dissanayake, Deepthi; Taylor, Donna B.
Abstract Cancer screening and surveillance programmes and the use of sophisticated imaging tools such as positron emission tomography‐computed tomography (PET‐CT) have increased the detection of impalpable lesions requiring imaging guidance for excision. A new technique involves intra‐lesional insertion of a low‐activity iodine‐125 (125I) seed and detection of the radioactive signal in theatre using a hand‐held gamma probe to guide surgery. Whilst several studies describe using this method to guide the removal of impalpable breast lesions, only a handful of publications report its use to guide excision of lesions outside the breast. We describe a case in which radio‐guided occult lesion localisation using an iodine 125 seed was used to guide excision of an impalpable posterior chest wall metastasis detected on PET‐CT.